The conflict between the Ayyubid and Romanians Seljuks in the Levant (1180-1219/ 576-616) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research centers around the conflict between the Ayyubid and Romanians Seljuks in the Levant. the causes behind these conflicts were mainly personal reasons and ambitions of expansion began in the reign of Alsultanyen Saladin and Kilij Arslan II Seljuk, when Arslan wanted to expand to south and included both Kisom and Raban forts. so the relationship between the two parties tensed and continued like that to the end of the two Sultans' eras. the relationship between the two countries wasn't even better after their death,too. tensions continued in the era of Aladel Ayoubi and Ghayath KaiKhosrow Seljuk and this conflict attracted several alliances which did not produce any result but deepening the disagreements and exhausting these alliances forces. Then the modern research talked about Seljuk Sultan Rukn al-Din KayKāvus's desire to seize Aleppo, his excuse was that the city had been under control of his ancestors. In this context, he made a contact with ALafdal Ayyubid and added him to his army because he knew the benefit he would obtain by one of the Ayyubid princes being on his side, but the Ayyubid were able to stand up to him and force him to withdraw. the relationship between the two parties continued to be tense till the Seljuk Sultan Rukn al-Din died, then Alaa Aldeen Keykubad took over his place and set his eyes on Armenia Minor to dominate it so he concluded a peace with the Ayyubid and married the king Aladel Ayoub's daughter to make the relationship between them stronger.